2022
DOI: 10.1002/art.42290
|View full text |Cite
|
Sign up to set email alerts
|

Association of 18F‐Fluorodeoxyglucose–Positron Emission Tomography Activity With Angiographic Progression of Disease in Large Vessel Vasculitis

Abstract: Objective To assess whether vascular activity seen on 18F‐fluorodeoxyglucose–positron emission tomography (FDG‐PET) scan is associated with angiographic change in large vessel vasculitis (LVV). Methods Patients with LVV were recruited into a prospective cohort. All patients underwent magnetic resonance angiography or computed tomography angiography and FDG‐PET imaging. Follow‐up imaging using the same imaging modalities was obtained ≥6 months later per a standardized imaging protocol. Arterial damage, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The key modification of this recommendation is the incorporation of the concept that vascular damage mainly occurs at sites of preceding vascular inflammation 3. This suggestion is based on the results of one study of 32 GCA and 28 TAK patients, reporting that 80% of territories subsequently developing angiographic changes (stenosis or aneurysms) during follow-up displayed a significant FDG-uptake at baseline 80. On the other hand, 92% of territories with baseline FDG-PET activity did not yield angiographic changes over time.…”
Section: Resultsmentioning
confidence: 99%
“…The key modification of this recommendation is the incorporation of the concept that vascular damage mainly occurs at sites of preceding vascular inflammation 3. This suggestion is based on the results of one study of 32 GCA and 28 TAK patients, reporting that 80% of territories subsequently developing angiographic changes (stenosis or aneurysms) during follow-up displayed a significant FDG-uptake at baseline 80. On the other hand, 92% of territories with baseline FDG-PET activity did not yield angiographic changes over time.…”
Section: Resultsmentioning
confidence: 99%
“…Five prospective studies providing information on the role of ultrasound in GCA patients 34 42 43 and FDG-PET in GCA 40 and in both GCA and TAK patients 44 for outcome prediction were included. No data were retrieved for the remaining imaging techniques.…”
Section: Resultsmentioning
confidence: 99%
“… 40 Another study with low RoB and a mixed population of both GCA and TAK patients revealed that territories with abnormal FDG uptake at baseline were at a higher risk of developing subsequent angiographic changes (OR 19.5, 95% CI 2.44 to 156). 44 …”
Section: Resultsmentioning
confidence: 99%
“…While the role of imaging as an outcome variable or component of remission is still unclear, there is the increasing evidence that, at least in GCA, imaging-determined signs of activity might have an impact on future relapses and vascular damage. [66][67][68] The present statement, however, should not be understood as a recommendation to reach imaging remission and/or negative acute phase reactants at all costs, rather the achievement of the target should…”
Section: Specific Recommendations Recommendationmentioning
confidence: 91%